A bilingual emotional advantage? An investigation into the effects of psychological factors in emotion perception in Arabic and in English of Arabic-English bilinguals and Arabic/English monolinguals. (April 2020) - Alqarni, Nada; Dewaele, Jean-Marc
Aims and objectives: While the debate on the cognitive bilingual advantage is ongoing, much less attention has been paid to the potential emotional advantage of bilinguals. The present study compared the performance of bilinguals and monolinguals in emotion perception (EP) in Arabic and in English and the differences in trait emotional intelligence (Trait EI). It also considered the relationship between Trait EI and EP scores. Methodology: 205 Arabic-English bilinguals, 71 Arabic monolinguals and 333 English monolinguals had to recognise anger, fear, sadness, disgust, surprise and happiness in 12 short audio-visual video clips (six in English and six in Arabic) embedded in an online questionnaire. The clips contained short conversations about day-to-day situations. Data and analysis: Nonparametric statistical analyses were used to explore the differences between bilinguals and monolinguals in EP in English and Arabic and to explore the relationship between Trait EI and EP. Findings: Bilinguals outperformed English monolinguals in the EP task in English but did not perform better than Arabic monolinguals in Arabic. Bilinguals scored higher on Trait EI than monolinguals, and Trait EI scores were significantly and positively correlated with EP scores. Originality: This study suggests that there is a small bilingual advantage for emotional and psychological domains. Significance: Bilingualism seems to have an effect on some personality dimensions and emotional skills.